2012
DOI: 10.1016/j.livsci.2011.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathological changes related to the use of ractopamine in swine: Clinical and pathological investigations

Abstract: The aim of the study was to investigate clinical and pathological modifications induced by treatment with different doses of the β2-agonist ractopamine (RAC) in pigs. Thirty-two eight-month-old LandracexLarge White pigs (mean weight, 102.8 ±6.7 kg) were treated with 0, 10 (R10), 20 (R20) and 40 (R40) mg/kg/diet of RAC for the last 35 days before slaughtering. Before and after treatment body weight was recorded, blood samples were collected for complete blood count and thyroid hormone concentration analysis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 37 publications
(22 reference statements)
0
3
1
2
Order By: Relevance
“…Thyroid and heart weight reduction was detected in swine following RA administration (Catalano et al, 2012). On the contrary, in the present experiment, the heart relative weight of veal calves did not undergo any change whereas the thyroid weight increased.…”
Section: Discussioncontrasting
confidence: 85%
“…Thyroid and heart weight reduction was detected in swine following RA administration (Catalano et al, 2012). On the contrary, in the present experiment, the heart relative weight of veal calves did not undergo any change whereas the thyroid weight increased.…”
Section: Discussioncontrasting
confidence: 85%
“…Ractopamine effects on market weight pig heart rates has been evaluated in 4 studies ( Table 12 ), but it is worth mentioning that 1 of these studies only reported raw treatment means (Ivers, unpublished data, Study #1). Catalano et al (2012) reported no difference in baseline resting heart rates at the end of the feeding period among pigs fed 0, 10, 20, or 40 mg/kg RAC. Meanwhile, the RAC effects on heart rate during marketing events (presence of unfamiliar human, handling, loading, transport, and unloading) are conflicting in the literature.…”
Section: Resultsmentioning
confidence: 93%
“…Sabe-se que determinadas doses de ractopamina geram alterações cardíacas por meio da ativação ou dessensibilização dos receptores beta adrenérgicos. Em alguns estudos, como o de Catalano et al (2012), as alterações observadas no coração foram dose independente. No seu estudo com suínos a alta dose de ractopamina gerou uma diminuição cardíaca, o que condiz com o presente estudo no qual os animais apresentaram um menor peso cardíaco quando comparados ao grupo controle.…”
Section: Ghunclassified
“…Com relação ao peso intestinal, de acordo com Catalano et al (2012), a ractopamina pode causar uma diminuição na concentração do hormônio da tireoide T3, responsável pela regulação térmica do organismo, por estimular de forma cruzada os receptores alfa adrenérgicos, então o intestino tende a aumentar para tentar equilibrar a temperatura corporal do animal.…”
Section: Ghunclassified